Breakthrough pressure and permeability of hydrophobic sands - Sheikh Sulaiman Bin Mohammad Bahajjaj (Nanyang Technological University, 2024)
Soil hydrophobicity refers to the diminishing of the soil's attraction to water. This study investigates the relationship between breakthrough pressure and permeability of sand at varying levels of hydrophobicity. Using fine and coarse sand treated with Tung oil to induce hydrophobicity, three experiments were conducted: sessile drop test, water-entry pressure test, and falling-head permeability test. Results indicate that increasing hydrophobicity hinders water penetration, requiring greater pressure for water to infiltrate both fine and coarse sands as hydrophobicity increases. Additionally, fine sand requires a greater breakthrough pressure compared to coarse sand due to its smaller pore size. Coarse sand exhibits decreasing permeability with increasing hydrophobicity, while fine sand maintains relatively constant permeability due to its initial small pore size distribution.